The surface chemistry of natural particles - Sposito, Garrison, 1939- (Oxford University Press, 2004)
"This book covers the development of both experiment and theory in natural surface particle chemistry. It emphasizes insights gained over the past few years, and concentrates on molecular spectroscopy, kinetics, and equilibrium as they apply to natural particle surface reactions in aqueous media. The discussion, divided among five chapters, is complemented by lengthy annotations, reading suggestions, and end-of-chapter problem sets that require a critical reading of important technical journal articles."-- Resumé vydavatele
Keywords: chemie povrchových jevů; adsorpce; fázová rozhraní; sedimenty; surface chemistry; adsorption; interfaces (physical sciences); sediments; monografie; elektronické knihy; monographs; electronic books